(In)securitization and illiberal practices on the fringe of the EU. Issue 1 (2nd January 2016) - Skleparis, Dimitris
ABSTRACT: Illiberal practices of liberal regimes have been extensively studied by critical security studies. The literature on risk emphasises the idea of imminent dangers and the logic of worst-case scenarios, which eventually unsettle the balance between security and liberty by always favouring the former in its most coercive and exceptional forms. This paper, by drawing on (in)securitization theory, attempts to explain how particular illiberal practices with respect to the control and management of immigration on the fringe of the EU become normalised. It argues that (in)securitization of immigration and illiberal practices are effects of the very functioning of a transnational field of (in)security professionals that are produced through the structural competition between different actors of this field over the definition of security and the appropriate control and management of immigration. In this respect, it uses Greece as a case study and draws on material gathered through interviews with Greek security professionals in Athens, Lesvos, Orestiada, and Alexandroupoli, and analysis of their discourse in dissertations they prepared during their study in police academies.